West Nile virus (lineage 2) detected for the first time in mosquitoes in Southern Bohemia: new WNV endemic area? - Rudolf, I; Rettich, F; Betášová, L; Imrichová, K; Mendel, J; Hubálek, Z; Šikutová, S (Epidemiologie, mikrobiologie, imunologie, 2019)
Here we report the first detection of lineage 2 of neuroinvasive West Nile virus (WNV-2) in mosquitoes collected in a fishpond area of the Trebon Basin in southern Bohemia during the 2018 mosquito season. A total of 6790 mosquito females belonging to the Culex modestus, Culex pipiens, and Coquillettidia richiardii species were investigated in 136 pools, and WNV RNA was detected in two of them. The WNV strain shares genetic homology with other WNV-2 strains isolated in southern Moravia as well as with those causing outbreaks in southern and central Europe. The results highlight the need for entomological surveillance of pathogenic arboviruses even in areas not yet affected (WNV-free areas). The South Bohemian Region (in addition to southern Moravia) is becoming another risk zone of autochthonous occurrence of West Nile fever in the Czech Republic.
Keywords: West Nile Fever; Animals; Coquillettidia richiardii; Česká republika; emerging zoonoses; Culex modestus; Female; zvířata; West Nile virus; Culex pipiens; Czech Republic; arboviruses; South Bohemia; mosquitoes; virus západního Nilu; západonilská horečka; ženské pohlaví; Culicidae